Changes That May Occur in Temperature, Rain, and Climate Types Due to Global Climate Change: The Example of Düzce - İsmail Koç (Turkish Journal of Agriculture: Food Science and Technology)
Global climate change is defined as a process that affects all living things and ecosystems globally and is claimed as the most critical problem of the current century. Turkey, which is shown as one of the most affected countries by this process, is among the “countries at risk.” It is stated that the temperature will increase throughout the country until 2100, and this increase may reach 6 ºC. In order to determine the possible effects of global climate change, it is necessary to predict how the climate structure and basic parameters may change. From this point of view, this study is aimed to determine the change of temperature and precipitation, climate types (according to De Martonne, Lang, and Emberger climate classification) which are the most critical climate parameters until 2050 and 2070 in Düzce, one of the important cities of our country. The current situation and possible changes in 2050 and 2070 have been compared using RCP 4.5 and RCP 8.5 scenarios. As a result of the study, the temperature, precipitation, and related climate types would change significantly throughout the province of Düzce, and this change will show itself as a significant temperature increase and change in precipitation regime. In addition, a shift in climate types towards continental climate types is predicted until 2070. In order to avoid the destructive effects of global climate change, it is recommended to take measures on a sectoral basis.